Edificio residencial (1998)
Edificio construído con estructura metálica y revestimientos de zin y pizzarra, con una técnica tradicional.
Keywords: MOURA, EDUARDO SOUTO DE; OPORTO; PORTUGAL; EDIFICIOS DE VIVIENDAS; ESTRUCTURAS METALICAS; MATERIALES; CHAPA; ACERO; PIEDRA